Irrigation water productivity as affected by water management in a small-scale irrigation scheme in the Blue Nile basin, Ethiopia - Demeku, S.; Descheemaeker, Katrien K.; Haileslassie, Amare; Amede, Tilahun (Cambridge University Press, 2011)
In Ethiopia, irrigation is mainly implemented in small-scale irrigation schemes, which are often characterized by low water productivity. This study reports on the efficiency and productivity of a typical small-scale irrigation scheme in the highlands of the Blue Nile, Ethiopia. Canal water flows and the volume of irrigation water applied were measured at field level. Grain and crop residue biomass and grass biomass production along the canals were also measured. To triangulate the measurements, the irrigation farm management, effects of water logging around irrigation canals, farm water distribution mechanisms, effects of night irrigation and water losses due to soil cracking created by prolonged irrigation were closely observed. The average canal water loss from the main, the secondary and the field canals was 2.58, 1.59 and 0.39 l s−1 100 m−1, representing 4.5, 4.0 and 26% of the total water flow respectively. About 0.05% of the loss was attributed to grass production for livestock, while the rest was lost through evaporation and canal seepage. Grass production for livestock feed had a land productivity of 6190.5 kg ha−1 and a water productivity of 0.82 kg m−3 . Land productivity for straw and grain was 2048 and 770 kg ha−1, respectively, for teff, and 1864 kg ha−1 and 758 kg ha−1, respectively, for wheat. Water productivities of the crops varied from 0.2 to 1.63 kg m−3. A significant volume of water was lost from small-scale irrigation systems mainly because farmers’ water application did not match crop needs. The high price incurred by pumped irrigation positively affected water management by minimizing water losses and forced farmers to use deficit irrigation. Improving water productivity of small-scale irrigation requires integrated interventions including night storage mechanisms, optimal irrigation scheduling, empowerment of farmers to maintain canals and proper irrigation schedules.